Personality matters in extremely demanding environments: A bed rest performance study - Goerke, Panja; Marggraf-Micheel, Claudia; Stelling, Dirk; Soll, Henning (Frontiers in Psychology, 2024)
Introduction Personality is a rather neglected aspect in bed rest studies. The aim of the study was to clarify which specific personality pattern may predict the performance of bed rest study participants. Materials and methods Personality traits were correlated with participants’ performance rated by the team running the study. The sample consisted of N = 68 participants who took part in one of four different studies. A broad set of personality traits correlated with different performance aspects (stability, perseverance, modesty, flexibility, compliance, likability, social adaptation). Results Emotional instability showed the highest correlations. Furthermore, participants with low aggressiveness, low empathy and low achievement motivation were rated as more suitable for a study. Additionally, participants with a high extraversion showed a higher social adaptation. Discussion The results contribute to the knowledge of the impact of personality in extremely demanding environments and provide first evidence for the identification of an ideal personality profile predicting performance of bed rest study participants.